Effects of bandlimited RF power amplifiers on LINC performance - Martin, Kevin M.
The growth of modern wireless communication standards demands faster data rates which, with increased bandwidth, may limit wideband, efficient, and linear operation of base stations due to their inherently bandlimited RF power amplifiers (RFPAs). Linearization with Nonlinear Components (LINC) is a transmitter architecture that has good potential on achieving high linearity and efficiency. Due to its signal separation process, LINC suffers from spectral regrowth, which requires the RFPA to have sufficient bandwidth (BW) response. This research centered on determining the required parameters of RFPA to meet standard linearity performance with and without bandwidth limitation. Simulations showed that LINC conforms with linearity only up to a certain power (Pin) in RFPA saturation region. Measurements at no BW limitation showed conforming linearity with headroom of 30 dB from Pin at 1dB compression. To maintain this, RFPA must have BW 7x greater than the input modulation BW. Narrower RFPA BW results in smaller operating region, which eventually saturates from BW less than 6x. Apart from behavioral model, the study also used circuit-level RFPA models. Results show a decrease in linearity with further saturation levels. This is suggestive of the plausibility of the process in determining boundaries to which the RFPA parameters can be based on. This study suggests the possibility of achieving desirable linearity within the recommended region of operation dictated by the maximum allowable input power and the minimum bandwidth of the RFPA branches.